RAPID DIAGNOSIS OF BOVINE LEPTOSPIROSIS BY LipL32 BASED POLYMERASE CHAIN REACTION - Balakrishna, G; Meenambigahi, T (Indian Journal of Veterinary Sciences and Biotechnology, 2015)
The present study was undertaken to diagnose acute cases of bovine leptospirosis by PCR. A total of 42 bovines serum samples suspected for leptospirosis were subjected to PCR to amplify LipL32 gene. The study revealed the amplicon size of 756 bp in 38 (90.47%) sera samples. The clinical signs in these positive cases included abortion, repeat breeders, jaundice and haemorrhagic mastitis. The present study indicated that the PCR which amplify the LipL32 is most sensitive, rapid and reliable method in diagnosing the leptospirosis in cattle. Since, LipL32 is conserved in all the pathogenic leptospires, it could be widely used for the diagnosis of leptospirosis in animals and human beings.